Multi-element mixed-doped organic small-molecule hole transport layer, preparation method and application thereof
By employing the "cocktail effect" of multi-component mixed metal salt dopants, the problem of balancing stability and photoelectric performance of perovskite solar cells with Li-TFSI dopants was solved, achieving a highly efficient and stable hole transport layer and improving the photoelectric conversion efficiency and stability of the device.
Patent Information
- Application Number
- CN202311335550.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2043-10-13
AI Technical Summary
Existing Li-TFSI dopants have an adverse effect on the long-term operational stability of perovskite solar cells, and it is difficult to balance photoelectric performance and stability.
By employing the "cocktail effect" of multi-component mixed metal salt dopants, a multi-component mixed doped organic small molecule hole transport layer is formed by mixing metal TFSI dopants such as Li-TFSI, K-TFSI, Na-TFSI, Cs-TFSI, Rb-TFSI, Ag-TFSI, Zn-(TFSI)2, Mg-(TFSI)2 and Ca-(TFSI)2. Combining the characteristics of different metal TFSI dopants, the conductivity and carrier mobility are improved.
High photoelectric conversion efficiency and stability of perovskite solar cells were achieved, while reducing the amount of dopants, decreasing hygroscopicity, and improving the overall performance of the device.
Smart Images

Figure CN117396048B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photovoltaic materials technology, specifically relating to a multi-component mixed-doped organic small molecule hole transport layer, its preparation method, and its application. Background Technology
[0002] Spiro-OMeTAD and its derivatives are classic hole transport materials suitable for perovskite solar cells, and are among the most widely used and effective hole transport materials currently available. However, due to the low conductivity and hole mobility of Spiro-OMeTAD itself, it is often necessary to improve hole transport performance by doping with other substances. Among these, the classic Li-TFSI dopant can significantly improve the conductivity and mobility of the hole transport layer, thereby greatly improving the photoelectric conversion efficiency of the device. Currently, the efficiency of perovskite solar cells based on Li-TFSI-doped Spiro-OMeTAD hole transport layers has reached as high as 25.7%.
[0003] However, the presence of LiTFSI dopants can negatively impact the long-term operational stability of perovskite solar cells, mainly in two aspects: (1) the hygroscopicity of Li-TFSI metal salts and their byproduct LixOy can induce the decomposition of the perovskite absorber layer; (2) Li + Migration into the perovskite absorber layer can also cause device failure, resulting in severe hysteresis. To address the negative impacts of current Li-TFSI dopants, some researchers have developed undoped hole transport materials or other non-Li M-TFSI dopants. However, these approaches often struggle to ensure good conductivity and carrier mobility in the hole transport layer, leading to suboptimal optoelectronic performance. In other words, it is currently difficult to find a suitable alternative dopant or hole transport material that can balance excellent optoelectronic performance and stability.
[0004] Therefore, how to achieve both the photoelectric performance of optoelectronic devices and significantly improve their stability is a technical challenge that perovskite solar cells are still striving to solve. Summary of the Invention
[0005] This solution provides a multi-component hybrid doped organic small molecule hole transport layer, its preparation method, and its application. It utilizes the "cocktail effect" of multi-component hybrid metal salt dopants to improve the doping efficiency of the organic small molecule hole transport layer, thereby enhancing the stability and optoelectronic performance of the optoelectronic devices prepared from the organic small molecule hole transport layer.
[0006] Firstly, this solution provides a method for preparing a hole transport layer of multi-component hybrid doped organic small molecules, comprising the following steps:
[0007] S1: Dissolving an organic molecular material in a nonpolar solvent at room temperature to obtain an organic molecular solution, wherein the organic molecular material is at least one of the spiro organic molecules;
[0008] S2: A doped solution is obtained by sequentially adding a cosolvent and an acetonitrile solution containing a multi-component mixed metal TFSI dopant to an organic molecular solution and stirring. The multi-component mixed metal TFSI dopant contains at least one of Li-TFSI, K-TFSI, Na-TFSI, Cs-TFSI, Rb-TFSI, Ag-TFSI, Zn-(TFSI)2, Mg-(TFSI)2, and Ca-(TFSI)2.
[0009] S3: Deposit the doping solution onto the perovskite absorber layer film to form a multi-component mixed-doped organic small molecule hole transport layer.
[0010] Different metal TFSI dopants have their own specific effects. High-valence metal TFSI dopants, such as Ca(TFSI)2, Mg(TFSI)2, and Zn(TFSI)2, have a very strong ability to adsorb oxygen. Even a small amount can cause the spiro organic molecular film to adsorb more oxygen, thereby accelerating the oxidation of the spiro organic molecular film and enabling the conductivity and carrier mobility of the hole transport layer of the small organic molecule to reach a good level in a very short time. For metal TFSI dopants composed of smaller metals, such as NaTFSI and KTFSI, although their ability to adsorb oxygen is very weak and the conductivity of the film they dopants is poor, their Na and K ions can migrate to the perovskite absorber layer to passivate defects. In addition to oxidizing and doping spiro organic molecular films, commonly used LiTFSI dopants allow Li ions to diffuse to the lower interface, forming a built-in electric field that is conducive to electron extraction. While using only high-valence metal TFSI dopants can yield Spiro-OMeTAD films with excellent mobility and conductivity, their performance in devices is unsatisfactory due to the lack of a built-in electric field and defect passivation capabilities. Using only low-valence metals NaTFSI or KTFSI, although defect passivation is possible, their poor oxidation doping ability results in poor conductivity and extremely low device efficiency. Using only conventional LiTFSI requires high doping levels to achieve good conductivity and maintain normal device performance, but this leads to the Spiro organic molecular film being highly hygroscopic, limiting device stability. Therefore, this solution employs a multi-component mixed metal TFSI dopant approach, retaining Li ions that can establish a built-in electric field while containing high-valence metal TFSI with strong oxygen adsorption capabilities and / or low-valence metal Na / K ions for defect passivation.
[0011] In the embodiments of this scheme, the multi-component mixed metal TFSI dopant must contain Li-TFSI.
[0012] In some embodiments, the multi-component mixed metal TFSI dopant includes Li-TFSI, high-valence metal TFSI, and low-valence metal TFSI, wherein the high-valence metal TFSI is selected from one or a combination of Ag-TFSI, Zn-(TFSI)2, Mg-(TFSI)2, Ca-(TFSI)2, Rb-TFSI, and Ag-TFSI, and the low-valence metal TFSI is selected from one or a combination of K-TFSI and Na-TFSI.
[0013] Preferably, the high-valence metal TFSI is selected from one or a combination of Mg-(TFSI)2 and Ca-(TFSI)2.
[0014] In some embodiments, the multi-component mixed metal TFSI dopant includes Li-TFSI and high-valence metal TFSI, wherein the high-valence metal TFSI is selected from one or a combination of Ag-TFSI, Zn-(TFSI)2, Mg-(TFSI)2, Ca-(TFSI)2, Rb-TFSI, and Ag-TFSI. Preferably, the high-valence metal TFSI is selected from one or a combination of Mg-(TFSI)2 and Ca-(TFSI)2.
[0015] In some embodiments, the multi-component mixed metal TFSI dopant includes Li-TFSI and low-valence metal TFSI, wherein the low-valence metal TFSI is selected from one or a combination of K-TFSI and Na-TFSI.
[0016] In some embodiments, the organic molecular material is at least one of spiro-OMeTAD, Spiro-mF, Spiro-TTB, Spiro-TAD, or Spiro-X60. Preferably, the organic molecular material is spiro-OMeTAD.
[0017] In some embodiments, the nonpolar solvent includes one or more combinations of chlorobenzene, toluene, o-dichlorobenzene, or chloroform.
[0018] In some embodiments, the co-solvent is tert-butylpyridine (tBP).
[0019] In some embodiments, the mass concentration of organic molecules in the doping solution is 65-85 mg / mL.
[0020] In some embodiments, the total mass concentration of the multi-element mixed metal TFSI dopant is 300-400 mg / mL, and the molar concentrations of the individual metal salts TFSI in the multi-element mixed metal TFSI dopant are in an equimolar ratio.
[0021] Preferably, the multi-component mixed metal TFSI dopant contains equimolar ratios of Li-TFSI, K-TFSI, Na-TFSI, Mg-(TFSI)2 and Ca-(TFSI)2.
[0022] Preferably, the multi-component mixed metal TFSI dopant contains equimolar ratios of Li-TFSI and Na-TFSI.
[0023] Preferably, the multi-component mixed metal TFSI dopant contains equimolar ratios of Li-TFSI, K-TFSI, and Mg-(TFSI)2.
[0024] Preferably, the multi-component mixed metal TFSI dopant contains equimolar ratios of Li-TFSI, Na-TFSI, and Mg-(TFSI)2.
[0025] In some embodiments, the method for depositing the doping solution on the perovskite absorber layer film includes, but is not limited to, liquid phase spin coating, liquid phase blade coating, liquid phase spraying, and liquid-gas combined methods. Regardless of whether liquid phase spin coating, liquid phase blade coating, liquid phase spraying, or liquid-gas combined methods are used to prepare the hole transport layer, this approach allows for the design of reasonable fabrication processes to achieve the fabrication of perovskite solar cells with high photoelectric conversion efficiency and high stability based on multi-component mixed-doped hole transport layers.
[0026] Secondly, this solution provides a multi-component hybrid doped organic small molecule hole transport layer, prepared according to the above-mentioned method for preparing a multi-component hybrid doped organic small molecule hole transport layer. The conductivity of this organic small molecule hole transport layer is within (1*10) -4 ~8*10 -3 S cm -1 Hole mobility is (2*10) -3 ~8*10 -3 cm 2 V -1 s -1 ).
[0027] Thirdly, this solution provides an optoelectronic device, including a multi-component mixed-doped organic small molecule hole transport layer prepared by the above method. In some embodiments, the optoelectronic device can be a single-junction optoelectronic device. When the optoelectronic device is a perovskite-based solar cell, it includes a transparent conductive substrate, an electron transport layer, a perovskite light-absorbing layer, a multi-component mixed-doped organic small molecule hole transport layer prepared by the above method, and a metal electrode arranged sequentially.
[0028] This invention first prepares a doping solution containing multi-component mixed metal TFSI dopants, then deposits the doping solution onto a perovskite thin film to obtain a hole transport layer thin film sample. This method utilizes the "cocktail effect" of the mixed metal TFSI dopants to reduce the dopant content in the hole transport layer while maintaining doping efficiency, suppressing the damage of hygroscopic dopants to the battery, thereby producing a solar energy device with higher stability. Furthermore, the corresponding optoelectronic device also exhibits higher photoelectric conversion efficiency. This invention is simple to operate, has significant effects, high repeatability, and is suitable for large-scale commercial production.
[0029] Compared with existing technologies, this solution has the following characteristics and beneficial effects:
[0030] (1) By using at least two metal TFSI salts as dopants in the hole transport layer of organic molecules, a multi-element mixed doping method is adopted to achieve the "cocktail effect" of mixed metal salt dopants.
[0031] To improve doping efficiency, the mixed metal salt dopant contains high-valence TFSI metals with strong oxygen adsorption capabilities, low-valence Na and K ions for defect passivation, and Li ions that can establish a built-in electric field. Therefore, the overall dopant dosage is significantly reduced, achieving better device efficiency and greatly reducing the hygroscopicity of the Spiro-OMeTAD film. This allows for achieving the same doping level with less dopant, thereby reducing the hygroscopicity of the hole transport layer film. Furthermore, by utilizing the advantages of each component in the mixed metal salt dopant, the device achieves excellent photoelectric performance and stability, thus balancing both photoelectric performance and stability.
[0032] (2) The method for preparing the hole transport layer of multi-component mixed-doped organic small molecules in this scheme is simple to operate, has significant effects, high reproducibility, and is suitable for large-scale commercial production. The formal single-junction optoelectronic device provided by this invention, which uses multi-component mixed-doped organic molecules as the hole transport layer, has higher photoelectric conversion efficiency and higher stability compared with optoelectronic devices based on classical LiTFSI single-doped organic molecules. Attached Figure Description
[0033] Figure 1 This is a schematic diagram of the photoelectric conversion efficiency of the optoelectronic device in the control group corresponding to Example 1.
[0034] Figure 2 This is a schematic diagram of the photoelectric conversion efficiency of the optoelectronic device in Example 1.
[0035] Figure 3 This is a box-type comparison diagram of the photoelectric conversion efficiency of the optoelectronic devices in Example 2 and Comparative Example 1.
[0036] Figure 4 This is a box-type comparison diagram of the photoelectric conversion efficiency of the optoelectronic devices of Example 3 and Comparative Example 1.
[0037] Figure 5 This is a box-type comparison diagram of the photoelectric conversion efficiency of the optoelectronic devices in Example 4 and Comparative Example 1.
[0038] Figure 6 This is a box-type comparison diagram of the photoelectric conversion efficiency of the optoelectronic devices in Example 5 and Comparative Example 1.
[0039] Figure 7 This is a box-type comparison diagram of the photoelectric conversion efficiency of the optoelectronic devices in Example 6 and Example 3. Detailed Implementation
[0040] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.
[0041] Those skilled in the art should understand that, in the disclosure of this invention, the terms "longitudinal," "lateral," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the above terms should not be construed as limiting this invention.
[0042] It is understood that the term "a" should be understood as "at least one" or "one or more", that is, in one embodiment, the number of an element can be one, while in another embodiment, the number of the element can be multiple, and the term "a" should not be understood as a limitation on the number.
[0043] Example 1
[0044] In this embodiment, the method for preparing the hole transport layer includes the following steps:
[0045] (1) At room temperature, 72 mg Spiro-OMeTAD was completely dissolved in 1 mL of CB to obtain a Spiro-OMeTAD solution as an organic molecule solution;
[0046] (2) At room temperature, Li-TFSI (68.6 mg), K-TFSI (76.2 mg), Na-TFSI (72.4 mg), Mg-(TFSI)2 (69.8 mg) and Ca-(TFSI)2 (71.7 mg) were dissolved in 1 mL of ACN and stirred on a magnetic stirrer until completely dissolved to obtain the first dopant solution;
[0047] (3) Add 40 μL of t-BP and 20 μL of the first dopant solution to 1 mL of Spiro-OMeTAD solution, heat at 50 °C for 5 min, and stir on a magnetic stirrer for 3 min to obtain the doped solution.
[0048] (4) Spin-coating a multi-component mixed-doped organic molecule solution onto a perovskite thin film to prepare a hole transport layer thin film.
[0049] Example 2:
[0050] In this embodiment, the method for preparing the hole transport layer includes the following steps:
[0051] (1) At room temperature, 72 mg Spiro-OMeTAD was completely dissolved in 1 mL of CB to obtain a Spiro-OMeTAD solution as an organic molecule solution;
[0052] (2) At room temperature, Li-TFSI (171.6 mg) and Na-TFSI (181 mg) were dissolved in 1 mL of ACN and stirred on a magnetic stirrer until completely dissolved to obtain a second dopant solution.
[0053] (3) Add 40 μL of t-BP and 20 μL of the second dopant solution to 1 mL of Spiro-OMeTAD solution, heat at 50 °C for 5 min, and stir on a magnetic stirrer for 3 min to obtain the doped solution.
[0054] (4) Spin-coating a multi-component mixed-doped organic molecule solution onto a perovskite thin film to prepare a hole transport layer thin film.
[0055] Example 3:
[0056] In this embodiment, the method for preparing the hole transport layer includes the following steps:
[0057] (1) At room temperature, 72 mg Spiro-OMeTAD was completely dissolved in 1 mL of CB to obtain a Spiro-OMeTAD solution as an organic molecule solution;
[0058] (2) At room temperature, Li-TFSI (171.6 mg) and Ca-(TFSI)2 (179.25 mg) were dissolved in 1 mL of ACN and stirred on a magnetic stirrer until completely dissolved to obtain a third dopant solution;
[0059] (3) Add 40 μL of t-BP and 20 μL of the third dopant solution to 1 mL of Spiro-OMeTAD solution, heat at 50 °C for 5 min, and then stir on a magnetic stirrer for 3 min to obtain the doped solution.
[0060] (4) Spin-coating a multi-component mixed-doped organic molecule solution onto a perovskite thin film to prepare a hole transport layer thin film.
[0061] Example 4:
[0062] In this embodiment, the method for preparing the hole transport layer includes the following steps:
[0063] (1) At room temperature, 72 mg Spiro-OMeTAD was completely dissolved in 1 mL of CB to obtain a Spiro-OMeTAD solution as an organic molecule solution;
[0064] (2) At room temperature, Li-TFSI (114.4 mg), K-TFSI (127.1 mg) and Mg-(TFSI)2 (116.4 mg) were dissolved in 1 mL of ACN and stirred on a magnetic stirrer until completely dissolved to obtain the fourth dopant solution;
[0065] (3) Add 40 μL of t-BP and 20 μL of the fourth dopant solution to 1 mL of Spiro-OMeTAD solution, heat at 50 °C for 5 min, and then stir on a magnetic stirrer for 3 min to obtain the doped solution.
[0066] (4) Spin-coating a multi-component mixed-doped organic molecule solution onto a perovskite thin film to prepare a hole transport layer thin film.
[0067] Example 5:
[0068] In this embodiment, the method for preparing the hole transport layer includes the following steps:
[0069] (1) At room temperature, 72 mg Spiro-OMeTAD was completely dissolved in 1 mL of CB to obtain a Spiro-OMeTAD solution as an organic molecule solution;
[0070] (2) At room temperature, Li-TFSI (85.8 mg), Na-TFSI (90.5 mg), Mg-(TFSI)2 (87.3 mg) and Ca-(TFSI)2 (89.6 mg) were dissolved in 1 mL of ACN and stirred on a magnetic stirrer until completely dissolved to obtain the fifth dopant solution;
[0071] (3) Add 40 μL of t-BP and 20 μL of the fifth dopant solution to 1 mL of Spiro-OMeTAD solution, heat at 50 °C for 5 min, and then stir on a magnetic stirrer for 3 min to obtain the doped solution.
[0072] (4) Spin-coating a multi-component mixed-doped organic molecule solution onto a perovskite thin film to prepare a hole transport layer thin film.
[0073] Example 6:
[0074] In this embodiment, the method for preparing the hole transport layer includes the following steps:
[0075] (1) At room temperature, 72 mg Spiro-OMeTAD was completely dissolved in 1 mL of CB to obtain a Spiro-OMeTAD solution as an organic molecule solution;
[0076] (2) At room temperature, Li-TFSI (171.6 mg) and FK209-Co(Ⅲ)-TFSI (299.5 mg) were dissolved in 1 mL of ACN and stirred on a magnetic stirrer until completely dissolved to obtain the sixth dopant solution;
[0077] (3) Add 40 μL of t-BP and 20 μL of the sixth dopant solution to 1 mL of Spiro-OMeTAD solution, heat at 50 °C for 5 min, and then stir on a magnetic stirrer for 3 min to obtain the doped solution.
[0078] (4) Spin-coating a multi-component mixed-doped organic molecule solution onto a perovskite thin film to prepare a hole transport layer thin film.
[0079] Comparative Example 1
[0080] In this embodiment, the method for preparing the hole transport layer includes the following steps:
[0081] (1) At room temperature, 72 mg Spiro-OMeTAD was completely dissolved in 1 mL of CB to obtain a Spiro-OMeTAD solution as an organic molecule solution;
[0082] (2) At room temperature, Li-TFSI (520 mg) was dissolved in 1 mL of ACN as the fifth dopant;
[0083] (3) Add 40 μL of t-BP and 20 μL of the fifth dopant solution to 1 mL of Spiro-OMeTAD solution to obtain a single-doped organic molecule solution;
[0084] (4) Spin-coating a multi-component mixed-doped organic molecule solution onto a perovskite thin film to prepare a hole transport layer thin film.
[0085] Fabrication of perovskite solar cell devices:
[0086] Fabrication of perovskite solar cell devices: SnO2 nanoparticle dispersion was spin-coated onto a cleaned ITO substrate and heated at 165°C for 35 minutes to obtain an electron transport layer. At room temperature, FAI (75 mg), MACl (13 mg), and pentamidine hydrochloride (2 mg) were dissolved in IPA (1 mL) and stirred on a magnetic stirrer until completely dissolved to obtain a first precursor solution. At room temperature, 645 mg of PbI2 was completely dissolved in 1 mL of DMSO and DMF (DMSO to DMF volume ratio of 4:1) to obtain a second precursor solution with a concentration of 1.4 M. The first and second precursor solutions were spin-coated sequentially onto an ITO substrate with a SnO2 electron transport layer, heated at 90°C for 1 minute, and then heated at 150°C for 10 minutes to prepare a perovskite thin film. Subsequently, the hole transport layer solutions from Examples 1-6 and Comparative Example 1 were spin-coated onto the perovskite film to prepare the Spiro-OMeTAD hole transport layer. Finally, a silver metal electrode was deposited to obtain a complete perovskite solar cell device.
[0087] Performance testing:
[0088] Photovoltaic conversion efficiency test: The photovoltaic conversion test was conducted under an AAA-level solar simulator, with a test step of 30ms and an effective area of 0.1cm². 2 The bias voltage is from -0.2 to 1.2V or from 1.2 to -0.2V.
[0089] Test in Example 1:
[0090] The optoelectronic devices in the experimental group were prepared using the multi-component mixed-doped organic molecular solution from Example 1, while the optoelectronic devices in the control group were prepared using the single-doped organic molecular solution from Comparative Example 1. The JV curves of the perovskite solar cells prepared in the control and experimental groups are shown below. Figure 1 and Figure 2 As shown, the photoelectric conversion efficiency of the optoelectronic device in the experimental group reached 24.2%, while the photoelectric conversion efficiency of the control group was only 22.5%. This indicates that the hole transport layer prepared by the method of the present invention can improve the photoelectric conversion efficiency of the optoelectronic device.
[0091] Test in Example 2:
[0092] The optoelectronic devices in the experimental group were prepared using the multi-component mixed-doped (Li and non-high-valence metal TFSI) organic molecular solution from Example 2, while the optoelectronic devices in the control group were prepared using the single-doped organic molecular solution from Comparative Example 1. The efficiency statistics of the perovskite solar cells prepared in the control and experimental groups are as follows: Figure 3 As shown, the solar energy device fabricated using an organic molecular solution containing two mixed dopants exhibits a significantly higher photoelectric conversion efficiency than the control group. REF represents a device fabricated using a hole transport layer prepared with a conventional doping method; LiNa represents a device fabricated using a hole transport layer containing a mixed dopant of Li-TFSI and Na-TFSI.
[0093] Test in Example 3:
[0094] The optoelectronic devices in the experimental group were prepared using a multi-component mixed-doped (Li and preferably high-valence metal TFSI) organic molecular solution as described in Example 3, while the optoelectronic devices in the control group were prepared using a single-doped organic molecular solution as described in Comparative Example 1. The efficiency statistics of the perovskite solar cells prepared in the control and experimental groups are as follows: Figure 4 As shown, the solar energy device fabricated using an organic molecular solution containing two mixed dopants exhibits a significantly higher photoelectric conversion efficiency than the control group. REF represents a device fabricated using a hole transport layer prepared by a conventional doping method; LiCa represents a device fabricated using a hole transport layer containing a mixed dopant of Li-TFSI and Ca-(TFSI)2.
[0095] Test in Example 4:
[0096] The optoelectronic devices in the experimental group were prepared using the multi-component mixed-doped organic molecular solution from Example 4, while the optoelectronic devices in the control group were prepared using the single-doped organic molecular solution from Comparative Example 1. The efficiency statistics of the perovskite solar cells prepared in the control and experimental groups are as follows: Figure 5 As shown, the solar energy device fabricated using an organic molecular solution containing three mixed dopants exhibits a significantly higher photoelectric conversion efficiency than the solar energy device in the control group. REF represents a device fabricated using a hole transport layer prepared by a conventional doping method; Li K Mg represents a device fabricated using a hole transport layer containing a mixed dopant of Li-TFSI, K-TFSI, and Mg-(TFSI)2.
[0097] Test in Example 5:
[0098] The optoelectronic devices in the experimental group were prepared using the multi-component mixed-doped organic molecular solution from Example 5, while the optoelectronic devices in the control group were prepared using the single-doped organic molecular solution from Comparative Example 1. The efficiency statistics of the perovskite solar cells prepared in the control and experimental groups are as follows: Figure 6 As shown, the solar energy device fabricated using an organic molecular solution containing four mixed dopants exhibits a significantly higher photoelectric conversion efficiency than the control group's solar energy device. REF represents a device fabricated using a hole transport layer prepared with a conventional doping method; Li, Na, Ca, and Mg represent devices fabricated using a hole transport layer containing a mixed dopant of Li-TFSI, Na-TFSI, Ca-(TFSI)2, and Mg-(TFSI)2.
[0099] Test in Example 6:
[0100] The optoelectronic devices in the experimental group were prepared using the multi-component mixed-doped (Li and non-preferred high-valence metal TFSI) organic molecular solution from Example 6, while the optoelectronic devices in the control group were prepared using the multi-component mixed-doped (Li and preferred high-valence metal TFSI) organic molecular solution from Example 3. The efficiency statistics of the perovskite solar cells prepared in the control and experimental groups are as follows: Figure 7 As shown, the solar energy device prepared with the preferred high-valence metal TFSI organic molecular solution exhibits a significantly higher photoelectric conversion efficiency than the solar energy device prepared with the non-preferred high-valence metal TFSI organic molecular solution. LiCa represents a device prepared using a hole transport layer containing a mixed dopant of Li-TFSI and Ca-(TFSI)2; LiCo represents a device prepared using a hole transport layer containing a mixed dopant of Li-TFSI and FK209-Co(Ⅲ)-TFSI.
[0101] This invention is not limited to the preferred embodiments described above. Anyone can derive other products in various forms under the guidance of this invention. However, regardless of any changes in shape or structure, any technical solution that is the same as or similar to this application falls within the protection scope of this invention.
Claims
1. A method for preparing a multi-component mixed-doped organic small molecule hole transport layer, characterized in that, Includes the following steps: S1: Dissolving an organic molecular material in a nonpolar solvent at room temperature to obtain an organic molecular solution, wherein the organic molecular material is at least one of the spiro organic molecules; S2: The co-solvent and the acetonitrile solution containing the multi-component mixed metal TFSI dopant are added sequentially to the organic molecular solution and stirred to obtain the doped solution. The total mass concentration of the multi-component mixed metal TFSI dopant is 300-400 mg / mL. The multi-component mixed metal TFSI dopant includes Li-TFSI, high-valence metal TFSI and low-valence metal TFSI. The high-valence metal TFSI is selected from one or a combination of Zn-(TFSI)2, Mg-(TFSI)2 and Ca-(TFSI)2. The low-valence metal TFSI is selected from one or a combination of K-TFSI and Na-TFSI. S3: Deposit the doping solution onto the perovskite absorber layer film to form a multi-component mixed-doped organic small molecule hole transport layer.
2. The method for preparing a multi-component mixed-doped organic small molecule hole transport layer according to claim 1, characterized in that, The high-valence metal TFSI is selected from one or a combination of Mg-(TFSI)2 and Ca-(TFSI)2.
3. The method for preparing a multi-component mixed-doped organic small molecule hole transport layer according to claim 1, characterized in that, The total mass concentration of the multi-element mixed metal TFSI dopant is 300-400 mg / mL, and the molar concentrations of the individual metal salts TFSI in the multi-element mixed metal TFSI dopant are in equimolar ratio.
4. The method for preparing a multi-component mixed-doped organic small molecule hole transport layer according to claim 1, characterized in that, The organic molecular material is at least one of spiro-OMeTAD, Spiro-mF, Spiro-TTB, Spiro-TAD, or Spiro-X60.
5. The method for preparing a multi-component mixed-doped organic small molecule hole transport layer according to claim 1, characterized in that, The co-solvent is tert-butylpyridine (tBP), and the non-polar solvent includes one or more combinations of chlorobenzene, toluene, o-dichlorobenzene, or chloroform.
6. A multi-component hybrid doped organic small molecule hole transport layer, characterized in that, The method described in any one of claims 1 to 5 is used to prepare the hole transport layer of the multi-component mixed doped organic small molecule.
7. An optoelectronic device, characterized in that, Includes the multi-component hybrid doped organic small molecule hole transport layer as described in claim 6.
Citation Information
Patent Citations
Perovskite solar cell, preparation method thereof and electric equipment
CN116568050A
